CRIMINAL OFFENSE AND FACEBOOK - Petrašinović, Stefan D. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
The development of modern internet technologies has provided numerous ways for mass communication of people. One of these ways is through social networks. With more than two billion users worldwide, Facebook is the most massive social network of today and a powerful tool for sharing a wealth of data, images and other materials through their profiles, which may even be publicly accessible to an indefinite number of individuals. With such capabilities, Facebook is a suitable tool for various abuses and for committing various offenses.It is a common situation for users to post different statuses, photos, snapshots through profiles, or post comments on statuses, photos or snapshots, of offensive content. From the point of view of our positive criminal law, the criminal protection of the honor and reputation of the individual, as intangible human values, is not in dispute in these situations. However, the question arises of the legal qualification of such incriminated conduct, that is, whether through these acts of the perpetrators the basic or qualified form of the offense of offenses referred to in Art. 170 of the Criminal Code, given the particular means of enforcement. The author points out the facts and circumstances that influence the legal qualification of the criminal offense of insult through Facebook, its appearance, as well as various possible ways of its realization by several persons.
Keywords: social networks, Facebook, criminal offense of insults, legal qualification, appearance forms